IoT data encryption algorithm for security - Kanaan Ismael, Marwan (2020)
This research project is about encryption simulation for IoT data. It is important to enhance the security system when sending and receiving the IoT data. Some of these data, especially the health information for a particular person is very sensitive. Therefore, there is a need to encrypt and protect the data from malicious attack. The technique proposed in this research is using Hash function and encryption method to protect the data. To show the working of the encryption, a simulation is performed. The simulation used is a MATLAB coding. By inserting the number of bit and size of the data with random plain text, the system is able to encrypt the data. The simulation results showing that the encrypted data is completely different from the original data or the data haven't encrypted. Upon encrypted, the data being protected and will be unknown to the malicious. At the end of this research project, the result concluded that the waveforms will show the encryption process.